Essays on fire sales by funds - Astorino, Paula Sanchez (2024)
Funds are a growing investment mechanism in Brazil. Besides their practical relevance, the opaque structure of funds poses a plethora of important research questiona. This thesis focuses on some of these inquiries. The first essay is concerned with describing the current stage in funds research. Through a careful literature review, we show the present research agenda uses newer methods, such as machine learning, to questiona that have been debated for a long time. Additionally, the integrative review identifies some gaps within the funds literature. The second paper, makes a case for the implementation of swing pricing rules for funds in Brazil. Negative news can have much deeper and broader impact than the loss of share value in a company. Other entities, such as funds and their investors, also suffer, once their returns are tied to the performance of the companies they carry on their portfolio. In that senae, negative information affects even those not directly linked to the news. This paper concerns itself with secondhand consequences showing how funds Jose value and, more important, how shareholders are affected. Our empirical findings demonatrate that the first shareholders to redeem their money from the funds affected by a shock hold a relevant advantage towards investors that take longer to redeem. The combination of fire sales and redemption forces funds into a vicious circle where additional losses in value lead to further redemption, a so forward. Using synthetic control methodology we advocate Brazilian legislation could benefit from allowing funds to use a swing pricing rule to end the so called first mover advantage. Still concentrating in fire sales, the third essay focuses on the accounting scandal of Brazilian e-commerce Americanas and the behavior of funds during and after this shock. Our empirical findings reveal that accounting quality seems to represent a mitigating factor for information asymmetry between buyers and funds, as shown in the research that supports this essay. Further on, we show the pattern of expected and discretionary trades of the funds carrying stock from Americanas differed from the pattern observed for the rest of the market.